Application of multi-targeted CAR-T cell therapy in B-cell acute lymphoblastic leukemia - CAO Jinjin, DU Juan, QU Shanna, ZHU Mingyu, WANG Yang, HU Han, LIU Binlei (Jichu yixue yu linchuang)
Chimeric antigen receptor-modified T (CAR-T) cell therapy, as a new type of cellular immunotherapy, has shown good clinical efficacy in the treatment of malignant hematological tumors, especially B-cell acute lymphoblastic leukemia. However, there are problems such as antigen loss and immune evasion in single-target selection, so multi-target therapy strategies are gradually gaining attention. Multi-target CAR-T can effectively avoid antigen escape caused by a single target by targeting multiple tumor-associated antigens at the same time, reduce the risk of recurrence, and is expected to improve the therapeutic effect. This paper primarily discusses the structural types of multi-target CAR-T cell therapy and its clinical trial applications in the treatment of B-cell acute lymphoblastic leukemia (B-ALL), aiming to provide future references for the treatment of B-ALL.